Benefits of Red Ginger for Obstetrics - Mesrida Simarmata (Institute of Computer Science (IOCS), 2022)
Midwifery is a problem that can be encountered during a woman's life cycle. If not handled properly, it can interfere with women's quality of life and even increase the number of maternal deaths, including primary dysmenorrhea and perineal injuries. Primary dysmenorrhea is a gynecological complaint that most often occurs in women, namely pain that occurs at the beginning of menstruation, while perineal injuries are wounds that occur during childbirth in the part between the vulva and anus. namely the use of red ginger (Zingiber officinale Var.Rosc.Rubrum). Objective: To find out the benefits of red ginger in obstetric cases Method: Literature study that describes the benefits of red ginger to obstetric cases Sample: 2 studies of red ginger in obstetric cases Results: Both studies found that red ginger is very beneficial in Obstetrics